2019
DOI: 10.1038/s41598-019-38946-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-Hexylresorcinol on Protein Expressions in RAW 264.7 Cells as Determined by Immunoprecipitation High Performance Liquid Chromatography

Abstract: 4-Hexylresorcinol (4HR) is a small organic compound that is used as an additive antiseptic and antioxidant, but its molecular properties have not been clearly elucidated. The present study explored the cellular effects of 4HR on RAW 264.7 cells by immunoprecipitation high-performance liquid chromatography (IP-HPLC) using 216 antisera. 4HR-treated cells showed significant decreases in the expressions of proliferation-related proteins, cMyc/MAX/MAD network, p53/Rb/E2F and Wnt/β-catenin signalings, epigenetic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…According to NIH toxicology report, 4HR has shown anticancer effects in various types of cancers [15]. As 4HR increases the apoptotic stress mediated by mitochondrial proteins [18], cancer cells seem to be more influenced by 4HR administration. Based on these findings, there has been no evidence that 4HR might increase the incidence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to NIH toxicology report, 4HR has shown anticancer effects in various types of cancers [15]. As 4HR increases the apoptotic stress mediated by mitochondrial proteins [18], cancer cells seem to be more influenced by 4HR administration. Based on these findings, there has been no evidence that 4HR might increase the incidence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, any clue of carcinogenic effect by 4HR on breast cancer cells was not found. In addition, we recently clarified the effect of angiogenesis and osteogenesis by 4HR is mediated not by estrogen, but by transforming growth factor-β1 [18,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). 4HR administered to M2-type macrophages expresses a high level of TGF-β1 [63,64]. Osteal macrophages (OsteoMacs) produce osteoblast activators, such as TGF-β [65], osteopontin [66], and bone morphogenetic protein 2 (BMP-2) [67].…”
Section: -Hexylresorcinol For the Immunomodulationmentioning
confidence: 99%
“…TGF-β1 is an important cytokine in wound healing [79]. Though the downstream signals from TGF-β1 are divergent, 4HR decreases TGF-β1 associated inflammatory reactions by inhibiting the NF-κB pathway [63]. In the diabetic animal model, 4HR ointment showed a substantial increase in capillary regeneration as compared to the untreated control (data submitted for publication).…”
Section: -Hexylresorcinol For the Immunomodulationmentioning
confidence: 99%